An Empirical Investigation into the Influence of Sealing Crimp Geometry and Process Settings on the Seal Integrity of Traditional and Biopolymer Packaging Materials. (13th August 2012) - Matthews, Jason; Hicks, Ben; Mullineux, Glen; Leslie, John; Burke, Andy; Goodwin, Jim; Ogg, Andrew; Campbell, Alan
<x xml:space="preserve">Abstract</x> This article presents the results of investigations to determine how process settings and crimp geometry affect the seal strength and integrity of traditional polyolefin and biopolymer flexible packaging materials. The results show agreement with previous studies where temperature and dwell time are found to be the dominant factors for both polyolefin and biopolymer films. Pressure and crimp geometry are shown to be secondary factors in the process, up to the point of squeezing the film into molecular contact. In general, it is shown that biopolymers exhibit similar sealing characteristics to more traditional films. Regarding the sealing crimp geometry, it is shown that the crimp pitch has little or no effect on sealing integrity for films with gauges between 25 and 40 µm. However, for the same gauge material, crimp angles more than 80° offer the greatest potential to gain higher seal strengths. It is further shown that with the cellulose and polylactic acid films tested, a higher seal strength can be produced with crimp pitches of 2 mm and lower. Also presented are some more general implications for guiding the selection of sealing crimp geometry and their usage with biopolymers. Copyright © 2012 John Wiley & Sons, Ltd.